Comparative Study of the Efficiency of Plant Extracts (Azadirachta Indica & Melia Azedarach) as a Natural Alternative to Kill Musca Domestica: Studi Komparatif Efisiensi Ekstrak Tumbuhan (Azadirachta Indica & Melia Azedarach) sebagai Alternatif Alami untuk Membunuh Musca Domestica - Shifaa Waleed Khaled (Academia Open, 2024)
This study represents a comprehensive comparison between the efficiency of extracts of (Azadirachta indica) and (Melia azedarach), which is considered a natural alternative to combating Musca domestica. These experiments were conducted using different concentrations (5%, 10%, and 20%) of the extracts. Plant on equal groups of insects, with mortality measured over a 6-hour period. Which led to the results showing that the extract of Azadirachta indica was more efficient in killing Musca domesticaat different concentrations, especially at a concentration of 20%, where the killing rate reached 86.67%, compared to the extract of Melia azedarach, which had a killing rate of 73.33% at a concentration of 20%. At a concentration of 5%, the efficiency of the two extracts was approximately equal (46.67%), while it increased in the extract of Azadirachta indica at concentrations of 10% and 20%, reaching Its kill rate is 66.67% and 86.67%, respectively, compared of Melia azedarach plant, which has a kill rate of 60.00% and 73.33%. This shows that seeds of Azadirachta indica plant have a faster and more effective effect compared to Melia azedarach seeds, especially at high concentrations. According to these findings, Azadirachta indica seed extract can be regarded as a natural remedy for Musca domesticaat, reducing the related health and financial harm, with the potential for In situations where low or medium quantities are needed, Melia azedarach seed extract is a useful substitute. Highlights: Azadirachta indica is more effective than Melia azedarach in killing Musca domestica. High concentration (20%) increases efficiency; Azadirachta indica achieves 86.67% mortality. Melia azedarach serves as a substitute for low-medium concentration use. Keywords: Azadirachta indica , Melia azedarach, Musca domestica, Plant extracts